Expired Air Carbon Monoxide Levels as a Marker of Passive Smoking In Pregnant Women (International Journal of Physiology, 2020)
Background and Aim: Smoking directly or indirectly has serious impact on health of an individual.During smoking various chemicals and toxic substances are released into the air such as nicotine, carbonmonoxide which can be inhaled by the people nearby indirectly. Pregnant mothers may passively inhalecarbonmonoxidewhen exposed to such environment. Maternal Carbon monoxide passes through placentaand enters foetalblood combine with foetalhaemoglobin forming foetal carboxy haemoglobin. Foetal carboxyhaemoglobin in turn makes oxygen unavailableto foetal tissues which could be the reason for various pooroutcomes in unborn foetus such as low birth weight, intra uterine growth retardation with higher rates ofperinatal mortality. This study is aimed at measuring the expired air carbon monoxide levels in passivelysmoking pregnant women that can be correlated with exposure to passive smoking.Method and Materials: 100 antenatal women of gestational age between 26 to 34 weeks with and withoutexposure to passive smoking were measured for carbon monoxide levels in their expired air usingsimple,portable non invasive carbon monoxidemonitor.Statistical Analysis: Data analysis was done with unpaired student t test. P value of